(untitled) (Scientific journal of the Fergana State University, 2024)
This article highlights the representation of the image of Khizr in such folk tales as “Kissai Ibrahim Adham”, “Kissai Said Nasimi”, “Qissai Mashrab”. Particular attention in the stories is paid to how skillfully are depicted the difficult periods in the lives of the heroes and the moments when spiritual forces come to their aid. The character of Khizr is described and interpreted based on the Holy Qur’an, other religious-scientific sources and folk views.